Personnel selection practice in South Africa: which tools are Human Resources practitioners using and why? - Buley, Stella (Organisational Psychology, 2025)
Personnel selection is a critical organisational process with significant implications for worker performance and organisational outcomes. However, existing research reveals a persistent science-practitioner gap, where Human Resources (HR) professionals often select personnel assessment tools based on factors other than predictive validity. This study investigates personnel selection practices in South Africa, a context with limited existing research, to understand current trends and the factors influencing HR practitioners' selection tool choices. Employing institutional theory as a theoretical framework, the research addresses two primary research questions: (1) What personnel selection practices are currently being used by HR practitioners in South Africa, and how do these compare to North American samples? and (2) To what extent do perceptual factors such as assessment tool diffusion, legality, applicant reactions, organisational self-promotion, predictive validity, and costs (i.e., utility) influence selection procedure choices? Quantitative survey data were obtained from HR professionals (N = 62) in South Africa to shed light upon the selection procedures being used in practice and why practitioners prefer certain methods over others. Analysis found markedly higher usage rates of selection procedures in South Africa in comparison to other samples, specifically regarding psychometric assessments. Factors relating to the extent to which a procedure is perceived as highly diffused and legally defensible were most salient to South African HR practitioners. Findings offer insights into the current state of assessment practices and potential areas for improvement.